If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(5x + 4) = 9 Reorder the terms: 3(4 + 5x) = 9 (4 * 3 + 5x * 3) = 9 (12 + 15x) = 9 Solving 12 + 15x = 9 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-12' to each side of the equation. 12 + -12 + 15x = 9 + -12 Combine like terms: 12 + -12 = 0 0 + 15x = 9 + -12 15x = 9 + -12 Combine like terms: 9 + -12 = -3 15x = -3 Divide each side by '15'. x = -0.2 Simplifying x = -0.2
| xy+3y=8y-20 | | x^3-17x^2+90x-140=0 | | 4a-3a=20 | | 7f-15=f+3 | | -16x^2+8t+8=0 | | 15x+19y=4 | | 7(q-4)+3(q-5)=-23 | | 3x*x+5-2x-1= | | 19x+15y=3 | | y+9=5(x+10) | | 3xsquared+5-2x-1= | | n-26=(-13) | | 8(3x-3y)-4(8x+3y)= | | 6e+7=2e+11 | | y=1.05e+15 | | 9x+9=6-(8x-4) | | 39x=64x+24 | | 10x+12+4x-3= | | 5y-6+y+53=8y+50-5y | | 13t-2=3t+38 | | 11f=5f+36 | | 6(4x-8)=32 | | -8=2c-3c | | xy=120 | | 6-3(6-6x)=0 | | 3.2x+6.5=9.2+11x | | v^2-6v=20+2v | | (3+6)+4=3+(6+4) | | 1(x-4)=-5 | | 2(x+5.75)=15.275 | | 69.8x+42=65 | | 12/k=24k |